KEDUDUKAN PENGADILAN TATA USAHA NEGARA DI INDONESIA - Khoiruddin Manahan Siregar (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2020)
This paper describes the State Administrative Court in Indonesia, then the main focus in this paper is regarding the position of the State Administrative Court institution in Indonesia. So to answer this main focus here the author uses the method of library study by tracing references relating to the topics discussed in this paper. The findings in the search conducted by the writer are that the position of the State Administrative Court has a strong position in solving the problems of state administration.